Magnesium isotope geochemistry in arc volcanism - Teng, Fang-Zhen (Proc Natl Acad Sci U S A, 2016)
Incorporation of subducted slab in arc volcanism plays an important role in producing the geochemical and isotopic variations in arc lavas. The mechanism and process by which the slab materials are incorporated, however, are still uncertain. Here, we report, to our knowledge, the first set of Mg isotopic data for a suite of arc lava samples from Martinique Island in the Lesser Antilles arc, which displays one of the most extreme geochemical and isotopic ranges, although the origin of this variability is still highly debated. We find the δ(26)Mg of the Martinique Island lavas varies from −0.25 to −0.10, in contrast to the narrow range that characterizes the mantle (−0.25 ± 0.04, 2 SD). These high δ(26)Mg values suggest the incorporation of isotopically heavy Mg from the subducted slab. The large contrast in MgO content between peridotite, basalt, and sediment makes direct mixing between sediment and peridotite, or assimilation by arc crust sediment, unlikely to be the main mechanism to modify Mg isotopes. Instead, the heavy Mg isotopic signature of the Martinique arc lavas requires that the overall composition of the mantle wedge is buffered and modified by the preferential addition of heavy Mg isotopes from fluids released from the altered subducted slab during fluid−mantle interaction. This, in turn, suggests transfer of a large amount of fluid-mobile elements from the subducting slab to the mantle wedge and makes Mg isotopes an excellent tracer of deep fluid migration.